Ragam Metode Tafsir yang dilakukan oleh para Ulama - Hakmi Hidayat; Muhammad Fathan Mubina; Febiana Sintia Maharani (CV. ITTC INDONESIA, 2024)
Qur'anic exegesis is an important topic of study because Islamic scholars have created a variety of techniques for reading the Qur'an to provide readers with a comprehensive and contextual knowledge. These scholars employ a variety of exegetical methods, such as tafsir isyari, tafsir bilmatsur, tafsir birrayi, and scientific exegesis. The foundation of Tafsir bil-ma'tsur is early Islamic tradition, derived from reliable sources like the hadiths of the Prophet and the opinions of his companions. Tafsir bil-ra'yi, on the other hand, is mostly dependent on the interpreter's own experience and logic and frequently integrates linguistic and philosophical analysis. Tafsir isyari, also known as symbolic exegesis, explores the hidden or esoteric meanings of Qur'anic passages and is frequently associated with Sufism. Scientific exegesis links Qur'anic verses to scientific discoveries in an effort to bring the holy text into line with modern understanding. This variety of methods shows academics' attempts to bring fresh insights into Islamic thought while catering to the requirements of various historical eras and cultural circumstances. Through a thorough and critical analysis, this study seeks to shed light on the creation and use of these strategies as well as their effects on Muslim religious beliefs and practices.